Harmonic compensated individual-phase control of four-leg inverters for microgrid applications - Lee, Jin Sung; Lee, Sang Hyeon; Lee, In Ho; Ju, Sung Nam; Lee, Kyo Beum (Journal of Power Electronics, 2023)
In this paper, harmonic compensated individual-phase voltage control of four-leg inverters is proposed for microgrid applications. Individual-phase control, which is one of the promising voltage control methods of four-leg inverters, ensures robustness for high load unbalance rates. However, the odd harmonics generated by nonlinear loads and dead time deteriorate the quality of load voltages under single-phase control. The proposed method compensates for the odd harmonics included in the load voltages to improve the output power quality. In the proposed method, band-pass and all-pass filters are used to generate the virtual components for the individual-phase control. Additionally, the harmonics are compensated in the synchronous reference frame using a resonant controller, while the fundamental components are controlled by proportional-integral controllers. With the proposed method, the total harmonic distortion of the load voltages is maintained at a low level under unbalanced and nonlinear load conditions. The effectiveness of the proposed method is demonstrated through simulation and experimental results.
Keywords: Control methods; Four-leg inverters; Harmonic; Individual phase controls; Load voltages; Microgrid; Nonlinear load; Odd harmonics; Phase voltage; Unbalanced loads; Four-leg inverter; Harmonics; Microgrid; Nonlinear load; Unbalanced load